Issues and Innovation for Setting and Infrastructure Management in the Islamic University of Lebanon in the Time of Pandemic - Jamal Haydar; Walid Fahs; Mohammad Ayache (Journal of Sustainability Perspectives, 2022)
The Islamic University of Lebanon (IUL) is committed to providing faith and knowledge as a source of inspiration for the Lebanese nation, citizen, state and society as a whole. IUL has paid special attention to the environment and to the green metrics when establishing the new campus in Wardanieh, the rules related to green buildings and the preservation of the environment were taken into account. The COVID-19 pandemic has created the largest disruption of education systems in human history, affecting nearly 1.6 billion learners in more than 200 countries. In this paper we will describe how the setting and infrastructure of Wardanieh campus has helped in managing the Covid-19 crisis at the university through different levels: the physical distancing, the effect of the large campus buildings area according to the campus population, moreover the large forest spaces, the natural ventilation of buildings, the sanitization and sterilization procedures with setting guidelines for Covid-19 such as the obligation of wearing masks. Furthermore, we will describe the influence of ICT technologies into education in many different ways for distance learning, and how the university has evolved its ICT infrastructure to support the increase in demand on the internet capacity and on university servers.Keyword: IUL university, Green, SDGs, Covid-19 prevention, education, settings and infrastructure